Grade IV splenic injury: When to consult interventional radiology-a case report and review of management protocols - Madhukar Dayal; Pratik Pandey; Abhay Kumar (Society of Gastrointestinal Intervention, 2024)
The spleen is one of the organs most commonly affected by blunt abdominal trauma. Splenectomy is often indicated for high-grade post-traumatic injuries and in patients who are hemodynamically unstable, while non-operative management (NOM) is considered for the remaining cases. Patients who have undergone splenectomy are at an increased risk of overwhelming post-splenectomy infection, leading to a shift in the consensus toward managing splenic trauma with spleen-preserving NOM approaches, such as splenic artery embolization, when possible. Patients with grade IV and V splenic injuries who are hemodynamically stable and do not have an active bleed are often candidates for prophylactic angioembolization. This intervention reduces the risk of re-bleeding, preserves splenic function, and decreases the likelihood of requiring a splenectomy. However, not all facilities have access to interventional radiology (IR). Through this case report, we emphasize the importance of using the period of conservative management to either consult with an IR specialist or transfer the patient to a center equipped with IR, given the high risk of re-bleeding or delayed rupture of the spleen. An additional unusual finding in our case was a re-bleed occurring beyond the typical interval for NOM as reported in most literature.